P8 Neurodevelopmental outcome in very preterm infants randomised to receive two different parenteral nutrition regimens: The SCAMP nutrition study. (27th April 2016) - Tan, M; Parry, S; Morgan, C
Abstract : Background: We have previously shown that increasing parenteral protein and energy intake using a Standardised, Concentrated with Added Macronutrients Parenteral (SCAMP) nutrition regimen ameliorates early head growth failure in very preterm infants (VPI). The effect was greatest in infants <27 weeks gestation. Head circumference (HC) is correlated with brain volume and later neurodevelopmental outcome. We hypothesised that the SCAMP nutrition regimen would improve later neurodevelopmental outcome when compared the control regimen. Aim: To compare neurodevelopmental outcome at 2–3.5 years in VPI randomised to receive SCAMP nutrition (12% glucose, 3.8g/kg/day protein/lipid) or a control standardised, concentrated PN regimen (10% glucose, 2.8g/kg/day protein/lipid). Methods: The ethically approved, double-blind study (ISRCTN: 76597892) was powered for the primary outcome (day 28 HC). Control parenteral nutrition (PN) was started within 6 h of birth. VPI (stratified into 24–26 and 27–28 weeks gestation) were randomised to either start SCAMP or remain on the control regimen. The consent process included neurodevelopmental assessment (Bayley III) all performed (parents and assessors blinded to original treatment allocation) by MT or SP between 2 and 3.5 years corrected gestational age. The raw scores of each subtest (Cognitive, Receptive and Expressive Communication, and Fine and Gross Motor) were converted to scaled scores and composite scores. A composite score of 100 is equivalent to normative mean and with 2SD below the mean at 70. Results: The original study randomised 150 infants to SCAMP (n = 74) and control (n = 76) groups respectively. Bayley III assessments were performed at home where possible in 38/62 SCAMP survivors and 39/63 control survivors. Table 1 summarises the composite score data for all infants and the 24–26 week stratum. P-values were obtained using unpaired t-tests or Fisher's exact test. Conclusion: This study did not show improved neurodevelopmental outcome with SCAMP versus control regimens. A parenteral nutrition study powered to investigate neurocognitive outcomes in infants <27 weeks gestation is required.